Equilibrium strategy-based optimization method for the coal-water conflict: A perspective from China. (1st September 2015) - Xu, Jiuping; Lv, Chengwei; Zhang, Mengxiang; Yao, Liming; Zeng, Ziqiang
Abstract: Environmental water problems have become increasingly severe, with the coal-water conflict becoming one of the most difficult issues in large scale coal mining regions. In this paper, a bi-level optimization model based on the Stackelberg–Nash equilibrium strategy with fuzzy coefficients is developed to deal with environmental water problems in large scale coal fields, in which both the groundwater quality and quantity are considered. Using the proposed model, and fully considering the relationship between the authority and the collieries and also the equilibrium between economic development and environmental protection, an environmental protection based mining quotas competition mechanism is established. To deal with the inherent uncertainties, the model is defuzzified using a possibility measure, and a solution approach based on the Karush-Kuhn-Tucker condition is designed to search for the solutions. A case study is presented to demonstrate the practicality and efficiency of the model, and different constraint violation risk levels and related results are also obtained. The results showed that under the environmental protection based mining quotas competition mechanism, collieries attempt to conduct environmentally friendly exploitation to seek greater mining quotas. This demonstrates the practicality and efficiency in the proposed model of reducing the coal-water conflict. Finally, a comprehensive discussion is provided and some propositions is given as a foundation for the proposed management recommendations. Highlights: A bi-level model for solving coal-water conflict is developed. The trade-off between financial revenue and environmental protection is analyzed. The trade-off among different decision makers' profit is analyzed. Application of the model in Lu'an coal mine is shown with 8 kinds of situations. Two management recommendations are given.